Modernist Women Poets Generations, Geographies and Genders - Dowson, Jane (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue showcases poets who enhance the breadth of modernist literary practices. The cohering concept is a complex relationship to both gender and modernity through original experiments with language. Leading scholars explore writers who both fit and extend orthodox modernist histories: Marianne Moore, H.D., Edna St Vincent Millay, Dorothy Parker, Katherine Mansfield, and Charlotte Mew were born around the cusp of the twentieth century and flourished during the 1920s and 1930s; Lynette Roberts, Helen Adam and Hope Mirrlees were contemporaries but publishing or recognition came later; the next generation can include Gwendolyn Brooks, Stevie Smith and Muriel Spark; Veronica Forrest-Thomson represents a third generation who published into the 1980s, while Frances Presley and M. NourbeSe Philip hinge this group with the contemporary poets Carol Watts and Natasha Trethewey, whose works continue and rejuvenate progressive stylistics. The essays offer new readings of both well-known and unfamiliar poets. They are truly groundbreaking in plundering diverse theoretical fields in ways that disturb any lingering notions of a homogenized women's poetry. The authors supplant into literary poetic analysis notions of geometry and mathematics, maritime materialities, tourism and taxonomy, architecture, classicism, folk art, Christianity and death, whimsy and empathy.